THE IMPACTS OF ZINC ON LIVER AND SERUM PROTEINS AND CHOLESTEROL LEVELS OF FISH (CIRRHINUS MRIGALA) - KUMAR, ANAND; DAHIYA, TEJPAL (The Bioscan, 2013)
The present investigation was aimed to observe the impacts of Zinc (Zn) on the protein levels in liver, serum and cholesterol of Cirrhinus mrigala fingerlings and experiments were designed having control without Zn and three treatments T1, T2 and T3 containing Zn at concentrations 0.01, 0.02, 0.04 ppm, respectively in triplicates. The decreasing trends were observed in the protein levels of liver tissue in C. mrigala with an increase in the concentrations of Zn from T1 then T2 to T3 i.e. 16.40% (56.00±0.45 μg/g), 32.83% (44.26±0.52 μg/g) and 47.76% (34.86±0.81μg/g), respectively w. r. t. control (T0) 67.10±0.45 μg/g for 45 days. The decline in liver proteins was found to be maximally i.e. up to 47.76% in liver proteins. The declines in serum protein level were observed in T1, T2 and T3 i.e. 4.76% (8. 00 ± 2.54 μg/g), 11.90% (7.33 ± 4.34 μg/g) and 24.06% (6.34±0.72 μg/g) at concentrations 0.01, 0.02, 0.04 ppm of Zn, respectively w. r. t. control (T0) 8.40±0.58(μg/g). After 45 days, the levels of cholesterol were increased with an increase in the concentrations of Zn in treatments T1, T2 and T3 and it was increased up to 69 % at 0.04ppm (T3). In conclusion, the levels of liver and serum proteins decrease while cholesterol increases when C. mrigala is subjected to Zn metal toxicity.